2005
DOI: 10.1016/j.ydbio.2005.06.023
|View full text |Cite
|
Sign up to set email alerts
|

Zebrafish ftz-f1a (nuclear receptor 5a2) functions in skeletal muscle organization

Abstract: Fushi-tarazu factor 1a (Ftz-F1a, Ff1a, Nr5a2) is a nuclear receptor with diverse functions in many tissues. Here, we report the function of ff1a in zebrafish muscle differentiation. In situ hybridization revealed that ff1a mRNA was present in the adaxial and migrating slow muscle precursors and was down-regulated when slow muscle cells matured. This expression was under the control of hedgehog genes, expanded when hedgehog was increased and missing in mutants defective in genes in the Hedgehog pathway like you… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…However, analysis of their targets demonstrated that several were involved in myogenesis regulation, suggesting that these miRNAs could participate in regulating muscle development through their target genes. For example, miR-200b has eight predicted targets, among which are three genes RECK, SLC38A2 and Nr5a2 , which encode proteins that are reported to be involved in muscle development [51-53]. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, analysis of their targets demonstrated that several were involved in myogenesis regulation, suggesting that these miRNAs could participate in regulating muscle development through their target genes. For example, miR-200b has eight predicted targets, among which are three genes RECK, SLC38A2 and Nr5a2 , which encode proteins that are reported to be involved in muscle development [51-53]. …”
Section: Resultsmentioning
confidence: 99%
“…Nr5a2 is the putative target of gga-miR-200b, gga-miR-128 and gga-miR-27b. Its product, the nuclear receptor transcription factor Nr5a2, has been reported to function during skeletal muscle organization [53]. Therefore, although little is known about the specific functions of several of these miRNAs (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…At this stage, endothelial cells stream into the previously avascular muscle primordium (Ruberte et al, 2002). While a few participating molecules are known (Sheela et al, 2005), the molecular basis for these alignments and separations is not known.…”
Section: Morphogenesis Of Head Musclesmentioning
confidence: 99%
“…Because of its decisive role in cell differentiation, LRH-1 is linked to multiple developmental pathways, including Hedgehog (8) and Wnt/␤-catenin (6,9,10) signaling. In particular, LRH-1 enhances transcription of multiple genes controlled by the regulatory Wnt/␤-catenin cascade.…”
mentioning
confidence: 99%